Agricultural socialized services to stimulate the green production behavior of smallholder farmers: the case of fertilization of rice production in south China - Shi, Fang; Cai, Baozhong; Meseretchanie, Abate; Geremew, Betelhemabraham; Huang, Yuangji (Frontiers in Environmental Science, 2023)
Agricultural socialized services (ASSs) system in China is being set up to turn smallholder farmers into key players in modern agricultural development. However, the effect of ASSs on the green production behaviour (GPB) of smallholder farmer is understudied. This study aims to explore the impact of ASSs on the GBP of smallholder farmers in the main rice production region of southern China. The probit model is employed to empirically examine the relationship between ASSs and smallholder farmers’ GPB based on data collected from 741 farmers in Hunan, Jiangxi and Zhejiang provinces. The findings show that ASSs have a significant and positive impact on smallholder farmers’ GPB. Farmers who have obtained ASSs tend to apply organic fertilizer and soil-tested formula fertilizer than the counters. ASSs promote the improvement of green agricultural productivity by directing farmers towards the adoption of green agricultural production practices. Our analysis urges policy-makers to involve the GPB of smallholder farmers in vigorously developing services to agricultural producers and promoting agricultural machinery services according to local conditions. The positive effect of ASSs on smallholder farmers’ GPB suggests the further strengthening of ASSs, for instance, by optimizing the public administration service system, establishing a joint service organization and creating a good financial and legal service environment.